Synthetic Drone Classification Dataset - Wisniewski, Mariusz; Rana, Zeeshan A.; Petrunin, Ivan (Cranfield University, 2022)
A dataset of synthetic drone images. Contains 4 categories: DJI Phantom, DJI Mavic, DJI Inspire, and no drone. 1,000 images in the training dataset, and 1,000 images in the validation dataset.
Keywords: Drones; Drone detection; convolutional neural networks; Drone identification